New Bis-Cyclometalated Iridium(III) Complexes with β-Substituted Porphyrin-Arylbipyridine as the Ancillary Ligand - Moura, Nuno M. M. (2022)
Funding Information: NMM Moura, VV Serra and A Bastos thank their research contracts (CDL-CTTRI-048-88-ARH/2018, and CDL-CTTRI-62-ARH/2018) which are funded by national funds (OE), through FCT–Fundação para a Ciência e a Tecnologia, I.P., in the scope of the framework contract foreseen in numbers 4, 5 and 6 of the article 23, of the Law Decree 57/2016, of August 29, changed by Law 57/2017, of July 19. This work was partially supported by the Scientific Society PROTEOMASS (General Funds) (Portugal), Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP-2019/19448-8) and Universidade de São Paulo. K.A.D.F. Castro thanks CAPES for the post-doctoral scholarship granted (PNPD/CAPES). Publisher Copyright: © 2022 by the authors.